Cyclization of RNA 3'-terminal phosphate by cyclase from HeLa cells proceeds via formation of N(3')pp(5')A activated intermediate. - Filipowicz, W (1985)
RNA 3'-terminal phosphate cyclase has been partially purified from HeLa cells. In the presence of ATP and Mg2+, cyclase preparations catalyze conversion of RNA 3'-terminal phosphate to the 2',3'-cyclic phosphodiester. The mechanism of 3'-phosphate cyclization was studied with oligoribonucleotides containing terminal 2'-deoxy- or 2'-O-methylribose. Incubation of these substrates with cyclase and ATP results in formation of the corresponding activated 3'-terminal structures, dN(3')pp(5')A and Nm(3')pp(5')A. It is proposed that an intermediate step in cyclization is transfer of the adenylyl group from ATP to the 3' phosphate of RNA. Rapid attack of the adjacent 2'-OH normally follows, resulting in elimination of AMP and formation of the cyclic phosphodiester. Cyclase preparations can be covalently labeled with [alpha-32P]ATP, suggesting that an earlier step in the cyclization reaction involves formation of an adenylylated enzyme intermediate.